JENIS SATWA LIAR YANG DIPERDAGANGKAN SEBAGAI BAHAN PANGAN DI KOTA PONTIANAK - Mirdat, Ignasius; Kartikawati, Siti Masitoh; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2019)
This research aims to analyze animal species which are in trade as livestock. In purpose of investigating the conservation status of animals, it is to review the animal species. Method of this research was descriptive with qualitative approach. Data analysis to be applied was survey. The samples of analysis were the ministerial regulation on environmental and forestry number 92 of 2018, CITES, and Constitution number 5 of 1990. Result of the research showed that there were nine sorts of animal that were in trade as livestock. The best sold sorts of animal are cobra snakes, monitor lizards, and squirrels. The supplies were from Ketapang, Pontianak, Purun, Rasau. From Kalimantan Tengah, the supplies were specialized in wild boars and cobra snakes. Based on the price, wild boars and turtles had been the most expensive which are Rp. 70.000/kg. Four variants of foods in menu included sauced, soy sauced, rica, and fried. There were five species of animals which are conserved based on the ministerial regulation on environmental and forestry number 92 of 2018 such as monitor lizards and turtles and the other species such as cobra snakes, bats, and squirrels which are on appendix CITES II.Keywords : Ethnozoology, Livestock, Wild Animals.